Оптимизация стандартной методики определения расчетного времени эвакуации людей - Polevoda Иван; Dmitrichenko Александр; Sobolevskiy С. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The improvement of standardized calculation model for evacuation procedures based on non-simultaneous approach for people flows is reviewed.